2021
DOI: 10.1016/j.clml.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Highlights of the Management of Adult Histiocytic Disorders: Langerhans Cell Histiocytosis, Erdheim-Chester Disease, Rosai-Dorfman Disease, and Hemophagocytic Lymphohistiocytosis

Abstract: Histiocytic disorders are an exceptionally rare group of diseases with diverse manifestations and a paucity of approved treatments, thereby leading to various challenges in their diagnosis and management. With the discovery of novel molecular targets and the incorporation of targeted agents in the management of various adult histiocytic disorders, their management has become increasingly complex. In an attempt to improve the understanding of the clinical features and management of common adult histiocytic diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…Skin manifestations may present as a rash (LCH) or lid xanthelasmas or xanthomas (ECD). Other system involvement may include cardiovascular, respiratory, polyadenopathy, and hepatosplenomegaly ( 81 , 82 ).…”
Section: Specific Hypophysitis Typesmentioning
confidence: 99%
“…Skin manifestations may present as a rash (LCH) or lid xanthelasmas or xanthomas (ECD). Other system involvement may include cardiovascular, respiratory, polyadenopathy, and hepatosplenomegaly ( 81 , 82 ).…”
Section: Specific Hypophysitis Typesmentioning
confidence: 99%
“…While its pathogenesis has not fully been unraveled, recent studies have shown that half of the patient population carries an activating mutation of the BRAF V600E protein, while mutations in the MAPK-ERK or PI3K-AKT pathway have frequently been observed in the other half. Despite new treatment options with BRAF kinase inhibitors in patients with BRAF V600E mutations or MEK-inhibitors in patients with MAPK-ERK mutations, the 5-year survival is less than 70 % and it is recommended to initiate pharmacological treatment in all ECD patients except in asymptomatic patients with bone involvement only or in patients with diabetes insipidus as the only manifestation [1,4] Because pathologic histiocytes can infiltrate virtually every tissue, ECD can present itself with a variety of symptoms, ranging from asymptomatic to multiorgan disease with fatal outcome. The variety of clinical presentations can make ECD a challenging diagnosis that requires a multidisciplinary approach in which histopathological, clinical, and radiological findings have to be analyzed in the right context.…”
Section: Introductionmentioning
confidence: 99%
“…Radiologic evaluation involves identifying osteosclerotic lesions in the femurs, preferably with Tc99 bone scintigraphy, which are present in almost 90 % of all ECD patients [4,5]. (FDG)-PET has a lower sensitivity with regard to identifying osseous lesions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations